Enhancing smallholder resilience through index-based crop insurance: Evaluation of the aMaizing Project in Kenya - Mwungu, Chris; Otieno, Felix; Njambi, Agnes; Ghosh, Aniruddha (2024)
Smallholder farmers in Sub-Saharan Africa remain highly vulnerable to climate-induced shocks, with Kenya’s agriculture sector facing acute risks due to drought. Despite growing recognition of crop insurance as a risk mitigation tool, adoption remains below 1% among smallholders, largely due to affordability, limited awareness, and distribution challenges. The aMaizing Crop Insurance Project was implemented across 15 Kenyan counties to improve smallholder resilience by promoting index-based crop insurance bundled with climate advisories, training, and complementary services such as credit and certified inputs. This report evaluates the effectiveness of two core interventions—SMS-based agro-advisories and training through village champions—based on baseline and endline surveys conducted in five representative counties. Advanced econometric methods were used to assess outcomes on yield, income, and food security. Findings show that insured farmers experienced a 315 kg/acre increase in maize yields, a 13.97% improvement in food security, and higher crop income. Adoption was influenced by proximity to markets, training exposure, and access to climate information. However, adoption remains low due to systemic barriers and behavioral biases. Gender-disaggregated analysis revealed that women faced greater challenges but reported higher perceived benefits when targeted with tailored support. The project’s end-to-end digitization of the insurance process improved transparency and efficiency, enabling faster registration and payouts. These findings underscore the importance of bundling insurance with value-adding services, designing gender-sensitive approaches, and strengthening trust through transparent systems. Policy recommendations include expanding education campaigns, addressing affordability, and leveraging public-private partnerships to increase insurance penetration and build long-term resilience among smallholder farmers.